FAKTOR YANG MEMPENGARUHI RISK DISCLOSURE PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI - Sugandha, Theodora Vania; Suhendah, Rousilita (Fakultas Ekonomi, Universitas Tarumanagara, 2020)
The purpose of this research is to determine the effect of board independence, firm size, profitability, and leverage of risk disclosure. This research uses 316 data from 52 manufacturing companies listed on the Indonesia Stock Exchange (IDX). This research uses computer program Eviews version 9.0. The results of this research indicate that board independence has no significant effect on risk disclosure, firm size has a significant positive effect on risk disclosure, profitability has no positive effect on risk disclosure, and leverage has no significant effect on risk disclosure.